Nursing care of patients with disability in the sheltered workplace - a case study - Bernadeta Jędrzejkiewicz; Marlena Anna Ogórek (Kazimierz Wielki University, 2019)
The worldwide beginner of the occupational healthcare was an Italian physician who lived at the turn of seventeenth and eighteenth century. The establishment date of occupational health care in Poland is 1953. The main aim of occupational health services is to protect health of workers from the adverse effects of the working environment on the health of employees. The tasks of occupational health services may be performed by a nurse. In this study, a case of a 58-old man with moderate disability employed in a sheltered workplace is presented.